2018
DOI: 10.1097/igc.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Enhanced Recovery After Surgery Program on Patients Treated for Gynecologic Cancer in the Community Hospital Setting

Abstract: The results from our investigation suggest that adhering to an ERAS protocol confers beneficial hospital length of stay and hospital cost outcomes, without compromising patient readmission rates. Additional investigation scrutinizing the impact of ERAS enactment with more defined study variables in a larger, randomized setting is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Our reported improvement in LOS and postoperative complication rate is also in keeping with the findings of a majority of ERAS retrospective studies in gynecologic oncology 15,20,30‐34 . Marx et al reported reduced LOS, from 7.3 days to 5.4 days ( P < .05), and decreased severe medical complications, from 14% to 2% ( P < .01), with their fast‐track rehabilitation program after ovarian malignancy surgery 35 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our reported improvement in LOS and postoperative complication rate is also in keeping with the findings of a majority of ERAS retrospective studies in gynecologic oncology 15,20,30‐34 . Marx et al reported reduced LOS, from 7.3 days to 5.4 days ( P < .05), and decreased severe medical complications, from 14% to 2% ( P < .01), with their fast‐track rehabilitation program after ovarian malignancy surgery 35 .…”
Section: Discussionsupporting
confidence: 89%
“…In the Canadian context, the net cost saving.s per patient was CAD$956 15 . In the American setting, savings ranged from US$2572 to US$7600 per patient, 20,32 and from a 15% to 25% reduction in cost overall 44,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ottensen et al showed that median LOS following vaginal surgery performed for utero-vaginal prolapse was also significantly lower in patients receiving ERAS protocols compared to those receiving conventional care [25]. The amount of intraoperative fluid intake and total fluid intake was also shown to be decreased with the implementation of the ERAS protocol in women operated on for gynecologic cancer [26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on cost data collected in trials of the enhanced recovery approach for colorectal and gynecologic surgery, it appears that the implementation of an ERAS protocol can lead to savings of US$2200-$2500 per patient treated. 77,78 The authors of an economic evaluation of the ERAS multi-site colorectal surgery program in Alberta estimated that every $1 invested in the ERAS protocol delivered a savings of $3.8 (range $2.4-$5.1) in return. 79 Further evaluation of ERAS protocols and implementation are necessary to continue assessing the true effect of cost and length of stay.…”
Section: Is Implementing An Eras Protocol Cost-effective?mentioning
confidence: 99%